The Impact of Digital Application Usage on Customer Experience, Satisfaction, and Loyalty in A Life Insurance Company - Alfi Yani Andranurviza; Heti Mulyati; Jono M Munnadar (School of Business, IPB University (SB-IPB), 2022)
Since 2016, XYZ Insurance has measured customer satisfaction using a CXI value but it has not shown the relationship of using self-servicing digital application to customer satisfaction. This research will examine the impact of usage of digital applications on customer experience, customer satisfaction, and customer loyalty at XYZ Insurance. The research is used non-probability sampling with the quota sampling method by taking survey from 203 respondents who have used the features in the eXYZ application at least 2 times,. The specified sample criteria are customers who have used the eXYZ application at least twice since downloading the application. In this research, with an expected error rate of 5%, the number of samples required is 349, from a population of 3800 customers. then the data is processed using SEM PLS. From this research it was concluded that usage of digital applications has a significant relationship and has a positive impact on customer experience, customer experience has a significant and a positive impact on customer satisfaction, customer experience does not have a direct positive impact on customer loyalty but it has indirect impact through customer satisfaction, and customer satisfaction has a significant and a positive impact on customer loyalty. The most important factors for customers when using digital applications are digital application innovation, the convenience, and perceived value to customers. Keywords: customer experience, customer loyalty, customer satisfaction, digital applications, insurance